Risk factors associated with preterm birth after a prior term delivery. (28th September 2015) - Wong, LF; Wilkes, J; Korgenski, K; Varner, MW; Manuck, TA
Abstract : Objective: The objective of this study was to assess the presence of newly acquired preterm birth (PTB) risk factors among primiparous women with no prior history of PTB. Design: Case–control study. Setting: Deliveries occurring within a large healthcare system from 2002 to 2012. Population: Women with their first two consecutive pregnancies carried to ≥20 0/7 weeks' gestation. Methods: Those delivering the first pregnancy at term and the second preterm ≥20 0/7 and <37 0/7 weeks (term‐preterm cases) were compared with women with a term birth in their first two pregnancies (term‐term controls). Social factors with the potential to change between the first and second pregnancies and intrapartum labour characteristics in the first pregnancy were compared between cases and controls. Main outcome measures: Risk factors for term‐preterm sequence. Results: About 38 215 women met inclusion criteria; 1353 (3.8%) were term‐preterm cases. Cases and controls were similar with regard to race/ethnicity and maternal age at the time of the first and second deliveries. Cases delivered their second pregnancy approximately 3 weeks earlier (35.7 versus 39.1, P < 0.001). In multivariable models accounting for known PTB risk factors, women with a caesarean delivery in the first pregnancy [adjusted odds ratio (aOR) = 2.20; 95% confidence interval (CI) 1.57–3.08], new tobacco use (aOR = 2.33; 95% CI 1.61–3.38), and an interpregnancy interval <18 months (aOR = 1.37; 95% CI 1.21–1.55) were at increased risk of term–preterm sequence. Conclusion: Caesarean delivery in the first pregnancy, new tobacco use, and short interpregnancy interval <18 months are significant risk factors for term‐preterm sequence. Women should receive postpartum counselling regarding appropriate interpregnancy interval and cessation of tobacco use. Tweetable abstract: Caesarean delivery in the 1st pregnancy is a significant risk factor for preterm birth following a term delivery. Tweetable abstract: Caesarean delivery in the 1st pregnancy is a significant risk factor for preterm birth following a term delivery.